Tinjauan Al-Quran dan Hadist Tentang Sifat-Sifat Pemimpin (Studi Literatur) - Rusmita, Rusmita; Siskawati , Oies Febria; Satriadi, Inong (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to explore verses and hadiths related to the characteristics of leaders, outline their implications in a modern context, and provide an in-depth understanding of how these principles can be applied in the effective management of Islamic educational institutions. This study uses a qualitative approach with a literature study method. The main data of this study comes from books and articles published on google scholar. Data collection was carried out using the keywords "characteristics of leaders", "review of the Qur'an on the nature of leaders" and "review of Hadith on the nature of leaders". Data analysis is carried out qualitatively through data reduction, data presentation, and conclusion drawn. The results of the analysis show that the leader is considered a caliph who is responsible for the mandate from Allah. Therefore, leadership must be carried out with caution and based on religious teachings. Islamic leaders must possess some very important traits. First, a leader must have noble morals that are reflected in his daily behavior and actions. This morality includes various aspects, such as honesty, trustworthiness, wisdom, and concern for others. The moral of a leader should be an example for the community. A leader must also be able to control himself. These skills include controlling emotions, acting impulsively, and the ability to make the right decisions